The emerging role of APC/CCdh1 in controlling differentiation, genomic stability and tumor suppression - Wäsch, R; Robbins, J A; Cross, F R (Oncogene, 2010)
Deregulation of the G1/G0 phase of the cell cycle can lead to cancer. During G1, most cells commit alternatively to DNA replication and division, or to cell-cycle exit and differentiation. The anaphase-promoting complex or cyclosome (APC/C) activated by Cdh1 coordinately eliminates positive cell-cycle regulators as well as inhibitors of differentiation, thereby coupling cell-cycle exit and differentiation. Misregulation of Cdh1 thus has the potential to promote both cell-cycle re-entry and either perturbed differentiation or dedifferentiation. In addition, APC/C Cdh1 is required to maintain genomic stability. As a result, loss of Cdh1 can contribute to tumorigenesis in the form of proliferation of poorly differentiated and genetically unstable cells.